(untitled) (Libellarium: journal for research in the field of information and related sciences, 2016)
The aim of this paper is to try to answer the question of students’ perception of e-book considering different forms of e-books students might have experience with. Questions of defining the e-book and attitudes toward e-book are considered separately. Research conducted by online questionnaire on student population show that the experience that students have with e-books mainly consists of pdf versions of printed books. Devices used for reading e-books are mainly desktop computers or laptops or in smaller degree tablets. E-readers are almost not used at all since the ownership of the e-readers among students is almost non-existent. That level of e-book experience influences students’ definition of e-book. Students mainly consider an e-book to be electronic version of printed book that is read on a computer. Considering the content that student mostly read on e-books it’s mainly scientific literature or exam materials. Fiction is almost exclusively read on paper. Given the choice of type of book students would in both cases rather chose paper, although in case of scientific literature and exam materials they are more open to e-books. Factor analysis was used to analyse characteristic that students recognize in e-books and result show three independent factors: Usefulness and practicality, Reading experience and Accessibility. Usefulness and practicality and accessibility was rated positively and reading experience negatively. These results are expected considering that students mostly read e-books on computers and not on dedicated reading devices.